Peatland initiation and carbon accumulation in the Falkland Islands. (15th May 2019) - Payne, Richard J.; Ring-Hrubesh, Fin; Rush, Graham; Sloan, Thomas J.; Evans, Chris D.; Mauquoy, Dmitri
Abstract: The Falkland Islands in the South Atlantic Ocean contain extensive peatlands at the edge of their global climatic envelope, but the long-term carbon dynamics of these sites is poorly quantified. We present new data for ten sites, compile previously-published data and produce a new synthesis. Many peatlands in the Falkland Islands developed notably early, with a fifth of basal 14 C dates pre-Holocene. Falkland Islands peats have high ash content, high carbon content and high bulk density compared to global norms. In many sites carbon accumulation rates are extremely low, which may partly relate to low average rainfall, or to carbon loss through burning and aeolian processes. However, in coastal Tussac peatlands carbon accumulation can be extremely rapid. Our re-analysis of published data from Beauchene Island, the southernmost of the Falkland Islands, yields an exceptional long-term apparent carbon accumulation rate of 139 g C m −2 yr −1, to our knowledge the highest recorded for any global peatland. This high accumulation might relate to the combination of a long growing-season and marine nutrient inputs. Given extensive coverage and carbon-dense peats the carbon stock of Falkland Islands peatlands is clearly considerable but robust quantification will require the development of a reliable peat map. Falkland Island peatlands challenge many standard assumptions and deserve more detailed study. Highlights: The Falkland Islands contain extensive and poorly-understood peatlands. Peatlands are notably old with many pre-Holocene in age. Long-term carbon accumulation rate is very variable between sites. One site has the highest recorded carbon accumulation rate for any global peatland. These unusual peatlands deserve further study.